Anti-Pasch optimal coverings with triples - Demirkale, Fatih; Donovan, Diane; Grannell, Mike (WILEY, 2021)
It is shown that for v not equal 7 , 8 , 11 , 12, or 13, there exists an optimal covering with triples on v points that contains no Pasch configurations.
Keywords: minimum covering with triples; optimal covering with triples; Pasch configuration; Steiner triple system; Mathematics